2017
DOI: 10.1016/j.aorn.2017.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Surgery Cancellations at a Pediatric Ambulatory Surgery Center

Abstract: Surgery cancellations are costly and can be frustrating for patients, their families, and the surgical team. Because of the inherent nature of an ambulatory surgery center, which only performs scheduled elective procedures, surgical cancellations typically result in wasted time and resources. Pediatric surgery cancellations can be mitigated with proper preoperative screening and communication between nurses and patients' guardians. To reduce the rate of cancellation at our pediatric ambulatory surgery center, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 9 publications
1
22
0
1
Order By: Relevance
“…Results also underscore the importance of developed interventions to reduce preventable cancellations. For example, research has shown that improved preoperative anesthesia interviews, 38 modifications to surgical scheduling procedures, 39 and increased communication between healthcare professionals and surgical patients 40 can help reduce elective surgical cancellation rates. Further investigation is warranted to address additional strategic intervention opportunities for reducing surgical cancellation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Results also underscore the importance of developed interventions to reduce preventable cancellations. For example, research has shown that improved preoperative anesthesia interviews, 38 modifications to surgical scheduling procedures, 39 and increased communication between healthcare professionals and surgical patients 40 can help reduce elective surgical cancellation rates. Further investigation is warranted to address additional strategic intervention opportunities for reducing surgical cancellation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Research on surgery cancellation has predominantly focused on the reasons for cancellation and implementation of different preventive interventions to reduce cancellations (Azari‐Rad et al, 2013; Ferschl et al, 2005; Gaucher et al, 2016; Lee et al, 2017; Singhal et al, 2014). To our knowledge, no previous studies have reviewed the literature on patients’ experiences of surgery cancellation.…”
Section: Introductionmentioning
confidence: 99%
“…Unplanned surgery cancellation (USC) is a widespread problem for many health care organizations, [16][17][18][19][20] which causes distress and inconvenience to patients, affects health care quality, wastes operating room resource, and leads to low operational inefficiency. Many studies reported that the incidence of USC was higher than 10%, even more than 40% in Low-and middle-income countries.…”
Section: Research-article2020mentioning
confidence: 99%